2007
DOI: 10.1016/j.bbamem.2007.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional recovery of electropermeabilized skeletal muscle in-vivo after treatment with surfactant poloxamer 188

Abstract: A critical requirement for cell survival after trauma is sealing of breaks in the cell membrane [M. Bier, S.M. Hammer, D.J. Canaday, R.C Lee, Kinetics of sealing for transient electropores in isolated mammalian skeletal muscle cells, Bioelectromagnetics 20 (1999) 194-201; R.C. Lee, D.C. Gaylor, D. Bhatt, D.A. Israel, Role of cell membrane rupture in the pathogenesis of electrical trauma, J. Surg. Res. 44 (1988) 709-719; R.C. Lee, J.F. Burke, E.G. Cravalho (Eds.), Electrical Trauma: The Pathophysiology, Manifes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 34 publications
3
41
0
Order By: Relevance
“…These IRE-induced signal alterations (ie, hyperintense zones on proton-density-and T2-weighted images and hypointense zones on T1-weighted images) were consistent with classic proton-density, T1, and T2 relaxation increases typically observed during acute episodes of tissue edema (24)(25)(26)(27). In a prior in vivo electropermeabilized skeletal muscle study, the formation of edema was qualitatively confi rmed by phase contrast photomicrographs of H-E-stained samples ( 28 ). Our fi ndings are consistent with previous gene therapy electrotransfer studies, which similarly apply high-voltage electric pulses to permeabilize cell in larger signal voids than those depicted on TSE images.…”
Section: Experimental Studies: Irreversible Electroporation: In Vivo supporting
confidence: 65%
“…These IRE-induced signal alterations (ie, hyperintense zones on proton-density-and T2-weighted images and hypointense zones on T1-weighted images) were consistent with classic proton-density, T1, and T2 relaxation increases typically observed during acute episodes of tissue edema (24)(25)(26)(27). In a prior in vivo electropermeabilized skeletal muscle study, the formation of edema was qualitatively confi rmed by phase contrast photomicrographs of H-E-stained samples ( 28 ). Our fi ndings are consistent with previous gene therapy electrotransfer studies, which similarly apply high-voltage electric pulses to permeabilize cell in larger signal voids than those depicted on TSE images.…”
Section: Experimental Studies: Irreversible Electroporation: In Vivo supporting
confidence: 65%
“…In agreement with these predictions, an electrical breakdown of the plasma membrane within nanoseconds after the onset of the electric pulse was demonstrated by fluorescence measurements with a voltage-sensitive dye [Frey et al, 2006]. Contrary to larger pores formed by conventional electroporation and having a lifetime of up to several minutes [Bier et al, 1999;Weaver, 2000;Collins et al, 2007], the nanopores are expected to be very short-lived. The estimates of nanopores' life span vary from nanoseconds to about 1 s maximum [Melikov et al, 2001;Vernier et al, 2003Vernier et al, , 2004Vernier et al, , 2006Gowrishankar and Weaver, 2006;Vasilkoski et al, 2006], which makes their detection problematic and their physiological significance questionable.…”
Section: Introductionsupporting
confidence: 53%
“…Axonal injury was considered but the relatively rapid resolution of the reduced CMAP amplitudes and the absence of significant denervation on needle EMG refutes this. One possibility is that the reduction of amplitude was because of fluid entering the muscle and dampening the evoked response similar to electroporation reported by Collins et al 25 The time course of abnormality is not typical of that seen in ischemic injury to the nerve. 26 Given that the conduction velocities and distal latencies of the same nerves in this subject were unchanged postperfusion, and that there was no evidence for nerve/muscle impairment by history or clinical evaluation, we concluded that these electrophysiologic abnormalities were not of clinical significance.…”
Section: Discussionmentioning
confidence: 83%